The effect of anaerobic thermophilic fermentation of organic waste on changes in the content of biogenic elements (Eurasian Journal of Ecology, 2023)
The influence of anaerobic thermophilic fermentation of raw materials of plant and animal origin on the change in the content of biogenic elements in the liquid and solid effluent fractions after a biogas plant (BSU) has been established. The transformation of organic compounds in the process of anaerobic digestion causes an alkaline reaction of the biogas effluent. Comparing samples of liquid fraction (fugate) and solid fraction (digestate) of waste from various raw materials (food plant waste with cattle manure and the addition of the biopreparation "Agrarka", pig manure and litter manure of cattle), it was found that the nitrogen and potassium content in the samples of the fugate exceeds the corresponding digestate values, but the phosphorus content is higher in the digestate (almost three times). According to the content of biogenic effluent elements after anaerobic thermophilic fermentation, waste after processing of food plant waste with cattle manure and the addition of the biological preparation "Agrarka" prevails. Liquid and solid fractions of biogas plant waste are enriched with ammonium nitrogen by more than 40-60% compared to the raw material, depending on the type of raw material. The fugate contains less than 4 to 10% dry matter and the main amount of potassium. Up to 80% of the mass fraction of nitrogen in the fugate is its ammonium form. Against the background of low ash content of digestate, the total carbon content is high (more than 30%).Keywords: effluent, fertilizer, feedstock, total carbon, humus formation, digestate, fugate.